Fe(ii) and Co(ii) N-methylated CYCLEN complexes as paraSHIFT agents with large temperature dependent shifts. Issue 3 (20th December 2017) - Tsitovich, Pavel B.; Tittiris, Timothy Y.; Cox, Jordan M.; Benedict, Jason B.; Morrow, Janet R.
Abstract : Fe(ii ) and Co(ii ) complexes with two types of methyl groups function as paraSHIFT agents for temperature registration. Abstract : Several complexes of Co(ii ) or Fe(ii ) with 1, 4, 7, 10-tetraazacyclododecane (CYCLEN) appended with 1, 7-(6-methyl)2-picolyl groups are studied as 1 H NMR paraSHIFT agents (paramagnetic shift agents) for the registration of temperature. Two of the complexes, [Co(BMPC)] 2+ and [Fe(BMPC)] 2+, contain methyl groups only on the methyl picolyl pendents. Two other complexes, [Co(2MPC)] 2+ and [Fe(2MPC)] 2+, contain picolyl groups and also methyl groups on the macrocyclic amines. All macrocyclic complexes are in high spin form as shown by solution magnetic moments in the range of 5.0–5.9 μ BM and 5.3–5.8 μ BM for Co(ii ) and Fe(ii ) complexes, respectively. The 1 H NMR spectra of both of the Fe(ii ) complexes and one of the Co(ii ) complexes are consistent with a predominant diastereomeric form in deuterium oxide solutions. The highly shifted methyl proton resonances for [Co(2MPC)] 2+ appear at 164 and −113 ppm for macrocycle and pendent picolyl methyls and show temperature coefficients of −0.58 ppm °C −1 and 0.49 ppm °C −1, respectively. Fe(ii ) complexes have less shifted methyl proton resonances and smaller temperature coefficients. The 1 H resonances of [Fe(2MPC)] 2+ appear at 105 ppm and −46 ppm with corresponding temperature coefficients (CT) of −0.29 ppm °C −1 and 0.22 ppm °C −1, respectively. The relatively narrow linewidths of [Fe(2MPC)] 2+, however, produce superior CT/FWHM values of 0.44 and 0.31 °C −1 for the N -methyl and picolyl proton resonances where FWHM is the full width at half maximum of the 1 H resonance. The crystal structure of [Co(BMPC)]Cl2 shows a six-coordinate Co(ii ) bound to the macrocyclic amines and two pendent picolyl groups. The distorted trigonal prismatic geometry of the complex resembles that of an analogous complex containing four 6-methyl-2-picolyl groups, in which only two picolyl pendents are coordinated.